Accessory Lower Lid Lacrimal Puncta - Smriti Sharma; Mandeep Tomar; Rajeev Tuli; Richa Dhiman; Maninder Singh; Ankush Sharma (Delhi Journal of Ophthalmology)
A 40 year old female presented with a history of watering in her left eye for the last 6 months. Her visual acuity was 6/6 bilaterally. On slit lamp examination there were presence of 2 puncta on the left lower lid. One of the punctum was slit like and the other punctum was round. On syringing, it was found that both the puncta were patent. Fluorescence dye disappearance test was done which revealed early disappearance of dye from the left eye as compared to the right eye. Dacrocystography was done which showed single patent nasolacrimal duct.